An International Mapping of Medical Care in Nursing Homes. (January 2019) - Ågotnes, Gudmund; McGregor, Margaret J; Lexchin, Joel; Doupe, Malcolm B; Müller, Beatrice; Harrington, Charlene
Nursing home (NH) residents are increasingly in need of timely and frequent medical care, presupposing not only available but perhaps also continual medical care provision in NHs. The provision of this medical care is organized differently both within and across countries, which may in turn profoundly affect the overall quality of care provided to NH residents. Data were collected from official legislations and regulations, academic publications, and statistical databases. Based on this set of data, we describe and compare the policies and practices guiding how medical care is provided across Canada (2 provinces), Germany, Norway, and the United States. Our findings disclose that there is a considerable difference to find among jurisdictions regarding specificity and scope of regulations regarding medical care in NHs. Based on our data, we construct 2 general models of medical care: (1) more regulations—fee-for-service payment—open staffing models and (2) less regulation—salaried positions—closed staffing models. Some evidence indicates that model 1 can lead to less available medical care provision and to medical care provision being less integrated into the overall care services. As such, we argue that the service models discussed can significantly influence continuity of medical care in NH.